2022
DOI: 10.1371/journal.pone.0265439
|View full text |Cite
|
Sign up to set email alerts
|

Crop and water productivity and profitability of broccoli (Brassica oleracea L. var. italica) under gravity drip irrigation with mulching condition in a humid sub-tropical climate

Abstract: Strategic irrigation planning and soil water conservation measure can be rewarding for increasing agricultural productivity in a humid subtropical climatic environment. Field experiments were conducted to evaluate broccoli yield response to crop water productivity (CWP), irrigation water productivity (IWP) and economics under varied irrigation regimes and mulching. Four levels of irrigation: surface irrigation at 1.0 IW/CPE (irrigation water to cumulative pan evaporation, I1), drip irrigation at 0.6 (I2), 0.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…According to Biswas et al [68], the higher crop water productivity (59.2 kg m -3 ) was obtained from the 50% water application under polyethylene mulch using drip irrigation. Patra et al [69] also reported that the maximum crop water productivity (11.49 kg m -3 ) was observed from the combination of drip irrigation, deficit irrigation and black plastic mulch (BPM) on broccoli crops (Figure 6). The minimum irrigation water level is advisable due to reduced deep percolation and increased water use from the crop root zone of the soil.…”
Section: Surface Mulchingmentioning
confidence: 95%
See 2 more Smart Citations
“…According to Biswas et al [68], the higher crop water productivity (59.2 kg m -3 ) was obtained from the 50% water application under polyethylene mulch using drip irrigation. Patra et al [69] also reported that the maximum crop water productivity (11.49 kg m -3 ) was observed from the combination of drip irrigation, deficit irrigation and black plastic mulch (BPM) on broccoli crops (Figure 6). The minimum irrigation water level is advisable due to reduced deep percolation and increased water use from the crop root zone of the soil.…”
Section: Surface Mulchingmentioning
confidence: 95%
“…The following graphical interpretation is developed based on the data obtained from Tufa et al [66]. Several researchers have recommended the use of deficit irrigation with mulching than non-mulching and conventional systems in the area of water scarcity [67,68,69]. On the other hand, the combination of drip irrigation and deficit irrigation with mulch had a significant value for the improvement of crop water productivity.…”
Section: Surface Mulchingmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite acknowledging the potential of efficient irrigation and mulching, research concerning their combined effects on broccoli growth, yield, and water productivity still needs to be completed. Patra et al [15], Yasmin et al [16], and Kumari et al [17] studies underscore the importance of irrigation methods and mulching materials in influencing these outcomes. This highlights the intricate interplay of factors affecting broccoli responses and emphasizes the significance of the proposed research.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the evapotranspiration rate of a crop is comparable to its requirement for water, which is the quantity of water the crop requires to replace the loss of water through evapotranspiration [5]. Therefore, irrigation water management is of the utmost importance [6] since water application is the most important factor determining the sustainability of agricultural cropping systems. Due to environmental degradation and climate change, freshwater is becoming increasingly scarce [7].…”
Section: Introductionmentioning
confidence: 99%